Reactive oxygen species in inflammation and tissue injury - Mittal, Manish; Siddiqui, Mohammad Rizwan; Tran, Khiem; Reddy, Sekhar P; Malik, Asrar B (Antioxidants & redox signaling, 2014)
Abstract Reactive oxygen species (ROS) are key signaling molecules that play an important role in the progression of inflammatory disorders. An enhanced ROS generation by polymorphonuclear neutrophils (PMNs) at the site of inflammation causes endothelial dysfunction and tissue injury. The vascular endothelium plays an important role in passage of macromolecules and inflammatory cells from the blood to tissue. Under the inflammatory conditions, oxidative stress produced by PMNs leads to the opening of inter-endothelial junctions and promotes the migration of inflammatory cells across the endothelial barrier. The migrated inflammatory cells not only help in the clearance of pathogens and foreign particles but also lead to tissue injury. The current review compiles the past and current research in the area of inflammation with particular emphasis on oxidative stress-mediated signaling mechanisms that are involved in inflammation and tissue injury.